PENGARUH ZAKAT PRODUKTIF TERHADAP TINGKAT PENDAPATAN MUSTAHIK DI LAZ INISIATIF ZAKAT INDONESIA (IZI) KOTA BENGKULU - Vidia Margaretha; Dharma Setiawan; Amir Mukadar (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Poverty remains a critical issue in Bengkulu Province, with the poverty rate reaching 14.04% as of March 2023. Productive zakat serves as a potential instrument for economic empowerment among mustahik (eligible recipients). This study aims to examine changes in mustahik income levels before and after receiving productive zakat and to assess the effectiveness of the program implemented by the Indonesian Zakat Initiative (IZI) LAZ in Bengkulu City. A quantitative approach with a descriptive method was employed. Primary data were obtained through questionnaires distributed to 30 mustahik recipients of productive zakat from IZI. Data analysis included validity, reliability, and normality tests, the Wilcoxon signed-rank test, and program effectiveness analysis. The findings indicate that productive zakat, provided in the form of business capital assistance, equipment, and skills training, significantly increased the income of mustahik. The Wilcoxon test confirmed a significant difference in income before and after receiving productive zakat. These results demonstrate that IZI's productive zakat program in Bengkulu City is effective in improving income levels and fostering economic independence among mustahik, making it a strategic tool for poverty alleviation and community empowerment.